A Study of Post Keynesian Attempts at Hiding Townshend’s Main Question to Keynes in His November 1938 Letter and Keynes’s Answer - BRADY, Michael (Theoretical and Practical Research in Economic Fields, 2024)
Keynes’s letter of December 7 th , 1938, provided a direct answer to Townshend, who asked Keynes the following extremely important question in his letter of November 25 th : “This is the nearest I can get to an analysis of the part played by the factor of confidence in the rationale of interest. I believe that its further logical analysis at a deeper level of generalization is connected with the part played by the weight of evidence in your theory of probability, but I cannot see just how …..” (Keynes 1979, 292; italics added). Now Townshend ‘s question actually is “Where in your A Treatise on Probability is your analysis supporting the connection between confidence in the GT and the weight of evidence?” Keynes’s response was direct and straightforward: “As regards my remarks in my General Theory , have you taken account of what I say on page 240 , as well as what I say at page 148, which is the passage I think you previously quoted…”. (Keynes 1979; italics added). The clue, given here by Keynes to Townshend, is to p.240 of the General Theory ; however, it relates directly, as we will see, to Keynes’s chapter XXVI of the A Treatise on Probability . This paper will trace out how Keynes provided Townshend with the clues needed to recognize Keynes’s modeling of the conventional coefficient in chapter XXVI; however, Townshend gave up and failed to take this last step.